2014
DOI: 10.1007/s11032-014-0164-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of seedling and adult plant resistance to leaf scald for stable resistance in barley

Abstract: Rhynchosporium secalis can overcome a single resistance gene of barley in a relatively short period of time. Novel genes and quantitative trait locis (QTLs) are therefore vital to control scald in barley. A population of 220 double haploid lines was developed from a cross of Vlamingh and WABAR2147, where Vlamingh showed adult plant resistance (APR) and WABAR2147 showed seedling resistance to a group of isolates. The population was tested for APR to scald under natural infection in two consecutive seasons in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Previous studies have identified multiple QTL conferring resistance to rhynchosporium on the distal end of chromosome 6H (Jensen et al 2002;Cheong et al 2006;Shtaya et al 2006;Wagner et al 2008;Wang et al 2014). While Cheong et al (2006) suggested that rhynchosporium resistance identified on 6HS in a Schooner/O'Connor population could be a new locus independent of Rrs13, due to the difficulty of comparing genetic maps and sparsity of molecular markers it was not clear whether this and other QTL represented alleles of Rrs13 or an entirely different resistance locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have identified multiple QTL conferring resistance to rhynchosporium on the distal end of chromosome 6H (Jensen et al 2002;Cheong et al 2006;Shtaya et al 2006;Wagner et al 2008;Wang et al 2014). While Cheong et al (2006) suggested that rhynchosporium resistance identified on 6HS in a Schooner/O'Connor population could be a new locus independent of Rrs13, due to the difficulty of comparing genetic maps and sparsity of molecular markers it was not clear whether this and other QTL represented alleles of Rrs13 or an entirely different resistance locus.…”
Section: Discussionmentioning
confidence: 99%
“…The QTL identified by Cheong et al (2006) was found using natural inoculum, and the position of the QTL peak (at marker ABG378), strongly suggests that the QTL effect represents an allele of Rrs18. A single major resistance gene identified in a Vlamingh x WABAR2147 DH population by Wang et al (2014) on 6HS has flanking markers 1_1166 and Bmag500, located at 7.47 Mb and 16.14 Mb respectively, putting this QTL also in the vicinity of Rrs18. The resistance gene on 6HS in WABAR2147 was shown to be effective irrespective of growth stage, so if the conclusion that this resistance is an allele of Rrs18 is correct, it would suggest that Rrs18 would provide an effective resistance in the field (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSR markers flanking the target gene were first integrated into the barley consensus map [ 35 ]. Sequences of the molecular markers in the regions were used to search the barley genomic database ( http://webblast.ipk-gatersleben.de/barley/viroblast.php ) to identify corresponding barley contigs.…”
Section: Methodsmentioning
confidence: 99%
“…This high variability gives it an advantage to quickly overcome the resistance of individual genes in barley in a relatively short period (Zhan et al 2008). To effectively control barley scald, continuous efforts on identification of novel genes and quantitative trait loci (QTLs) are therefore vital to keep pace with pathogen development (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%